Provide a model to identify the effect of the occurrence of business cycles on financial uncertainty in the stock market Developed countries - Shirbandi, Hossein (2021)
The main purpose of this study is to provide a model to identify the effect of the occurrence of business cycles on financial uncertainty in the stock market of developed countries. This research is an experimental research and panel data has been used to test the hypothesis. The statistical population of the study is developed countries. We grouped the countries based on high per capita income according to the UN Human Development Report. Data were also collected from the World Bank and 21 developed countries were selected as the sample size. According to the results of coefficients of independent variables (financial leverage, interest rate, inflation, time, recessionary business cycles and boom business cycles) which are all significant, ie their P-VALUE is less than 0.05, so we can conclude a significant effect. On financial uncertainty (variance of S&P index growth rate). Also, considering that the coefficient of determination of the regression model (R2) is equal to 0.984 and is close to the number one, that is, the Fisher test (F) is significant (its probability is less than 0.05), so the regression model is justifiable and acceptable. Hypothesis H0 is therefore rejected and Hypothesis H1 is accepted with 95% probability, or in other words, business cycles have a significant effect on financial uncertainty in the stock market of developed countries.